Ethical Consumerism and Trade Liberalization: A Comparative Legal Analysis of Halal Regulatory Regimes - Kamran Abdullayev; Elay Yusifli Elshad; Zohaib Hassan Sain; Ahmad Maulidizen (Journal of Islamic Law and Legal Studies, 2025)
This study provides a comprehensive comparative legal analysis of halal regulatory regimes within the broader context of ethical consumerism and global trade liberalization. Using a qualitative library research approach, the study examines diverse national and regional regulatory models—including Malaysia’s centralized system, Indonesia’s hybrid framework, and decentralized certification practices in GCC and Western jurisdictions. The findings indicate that divergent legal philosophies, inconsistent certification processes, and fragmented enforcement mechanisms create significant barriers to mutual recognition and international market integration. Ethical consumerism intensifies demands for transparency, authenticity, and integrity, yet weak oversight in several regions perpetuates fraud, mislabeling, and supply chain vulnerabilities. Trade liberalization further complicates the landscape, as variations in halal standards often function as technical barriers to trade, disproportionately affecting SMEs. The study highlights the growing relevance of blockchain, AI, and digital traceability as potential solutions to enhance integrity, harmonize standards, and improve global halal governance. Ultimately, the analysis underscores that achieving balance between ethical consumer protection and liberalized trade requires collaborative regulatory reforms, robust oversight, and technologically supported verification systems capable of fostering trust and facilitating global market access.